The need for co-evolution of groundwater law and community practices for groundwater justice and sustainability: Insights from Maharashtra, India - Gabriela Cuadrado-Quesada; K.J. Joy (Water Alternatives, 2021)
With groundwater becoming the mainstay for meeting water requirements for life and livelihoods, countries around the world are experimenting with law reforms in order to establish some guiding rules for its use, distribution and protection. A fundamental question about law reforms is the degree to which they incorporate justice and sustainability. This article, in responding to this question, focuses on Maharashtra, India. We base our response on a content analysis of the 2009 Maharashtra Groundwater (Development and Management) Act; the 2018 Maharashtra Groundwater (Development and Management Draft Groundwater Rules; 1 and a village case study. Primary data was collected in Pune, Mumbai, and Hivre Bazar village; this included an empirical analysis of 47 in-depth interviews, participation in a number of village meetings and open-ended discussions, and direct observations of groundwater practices. Our analysis led to three conclusions. First, the 2009 Groundwater Act and the 2018 Draft Groundwater Rules are primarily driven by concern for sustainability of the resource, especially in areas where the water table is steadily declining, but when it comes to groundwater justice, no proactive measures are suggested in either the 2009 Groundwater Act or the 2018 Draft Groundwater Rules. Second, there are certain core factors identified at the local level that we believe to be fundamental in facilitating sustainability and – to a lesser extent – groundwater justice. These factors include a community’s ability to: (1) acknowledge that there is a crisis and display a willingness to engage with it; (2) create a rule-bound community groundwater resource; (3) demonstrate leadership and the feeling of community; and (4) utilise awareness, information and knowledge. Our third conclusion is that there is a need for the co-evolution of community practices and state-led groundwater law; such a co-evolution has the potential to put in place arrangements around groundwater that can support both groundwater justice and sustainability.